Fernand Khnopff’s Logogriphic Method: a Case Study of I Lock my Door upon Myself - Klyushina, Elena V. (Actual Problems of Theory and History of Art, 2016)
Named after the apt expression by Hermann Bahr, Khnopff’s logogriphic method has been studied on the basis of the detailed iconographic analysis of the artist’s masterpiece I lock my door upon myself. The author claims that the painter composed his pieces on the principle of poetic riddles leaving for a viewer a number of clues in the form of the title, iconographic prototypes, or the elements of the composition requiring a certain visual effort. The key to understanding I lock my door upon myself is its title which directly quotes the line of the sonnet by Christina Rossetti. The researcher particularly emphasizes the need to preserve the title of the painting in its authentic English version. It is significant in the view of the fact that in Russian art history the title of Khnopff’s painting is often translated as “The Hermit”. According to the author, such a translation is not valid, because it misinterprets the true title of the masterpiece and entails a number of potential errors in the analysis of its iconographic and semantic features. The article raises some issues that are important for the understanding of Fernand Khnopff’s creativity, such as Anglophile and James Whistler’s influence on Belgian art in the first half of the 1880s, the peculiarities of visual perception of classical antiquity, or the problem of the representation of hypnotic trance in art and culture of the 1890s. The other significant issue is the influence of the art of the Northern Renaissance on Belgian masters.
Keywords: symbolism; art of Belgium; pre-Raphaelites; hypnosis; fin de siècle; Fernand Khnopff; Christina Rossetti